The Extent to which Teachers of Deaf and Hard of Hearing Students in the Primary Stage use Augmented Reality Applications and the Barriers they Face - Alghamdi, Mohammed Saleh; Alzahraney, Turki Samah (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the extent to which teachers of deaf and hard of hearing students use augmented reality applications and the barriers they face. The descriptive survey method was used, and the study tool consisted of a questionnaire was consisted of (29) items divided into two main axes that discuss the reality and barriers to the use of augmented reality applications by teachers of deaf and hard of hearing students. The study sample included (157) male and female teachers of deaf and hard of hearing students in Makkah Al-Mukarramah region. The study reached a set of results, the most important of which was the use of augmented reality applications with a low degree with a mean of (2.58) and a relative weight of (29.6%) by teachers of deaf and hard of hearing students, and the existence of a high level (3.67) of barriers facing the use of augmented reality applications by them. The results also showed that there were no statistically significant differences in the averages of the total score for the measure of the extent of using augmented reality applications in teaching deaf and hard of hearing students and the barriers they face due to the following variables: gender (0.121), number of years of practical experience (0.605), training courses in the field of augmented reality (0.131), the place of work (0.079), the city in which they work (0.079), and the educational qualification (0.857). In light of the results of the current study, the researchers recommend a number of recommendations, the most important of which are: increasing the level of interest of the school administration in preparing special classrooms for deaf and hard of hearing students to use augmented reality in their education within the school, and providing modern applications that support augmented reality technology in the field of teaching deaf and hard of hearing students, improving the infrastructure of schools in line with the use of augmented reality technology, and the need of seeking the help of specialists and experts to train teachers and help them have sufficient experience to use augmented reality applications in teaching deaf and hard of hearing students, and increasing the number of training courses provided by the school administration to them.